Determining the Osmolality Threshold for Sickle Cell Erythrocyte Hemolysis - Richardson, Victoria M.; Woollen, M. T. Kay; Anong, William A. (New Frontiers in Medicine and Medical Research Vol. 15, 2021)
Background: Fluid intake is critical for metabolic and physiological processes to function properly in a homeostatic environment. When compared to other cells, normal red cells are more resilient to fluctuations in serum osmolality, remaining intact when serum osmolality drops to as low as 190 mOsM from the 270-290 mOsM reference interval. The ability of the membrane to deform/reform under shear confers strong resistance to variations in serum osmolality to red cells. Although normal red cells are resilient, the osmolality threshold for hemolysis of abnormal red cells such as sickle cell blood remains unclear. The major goal of this research was to identify the osmolality threshold for sickle cell hemolysis in comparison to normal red cells. Methods: Red cells were prepared and subjected to a solution of varied osmolality ranging from 290 to 65 mOsm of sodium chloride, as stated in the procedures section. Following incubation, the supernatant and pellets were examined using western blotting techniques for haemoglobin (spectrometry) and glycophorin A (GPA) concentration. Results: While normal red cells have an osmolality threshold of 190 mOsM, sickle erythrocytes have an osmolality threshold of 170-mOsM. Both cells ruptured rapidly -displaying an S-shaped-like “cooperativity” pattern. Complete (100%) hemolysis occurred at \(\le\)150-mOsM. The hemoglobin retained in pellets decreased to ~50% (normal red cells) and ~20% (sickle red cells) when solution osmolality drops to 65-mOsM. Conclusion: Sickle cell erythrocytes are more resilient than normal red cells to serum osmolality changes. This research sheds light on how normal and sickle cell people react to variations in serum osmolality during dehydration and rehydration. Intravenous fluids are routinely used as adjuvant therapy to relieve pain and slow or reverse the sickling process. As a result, regulating electrolytes and fluid volume during acute pain episodes could help African Americans, who are disproportionately affected by sickle cell disease.